Patients with asthma have a higher risk of rheumatoid arthritis: A systematic review and meta-analysis - Nipith Charoenngam (2020)
© 2020 Elsevier Inc. Objective: This study aimed to investigate whether patients with asthma have a higher risk of incident rheumatoid arthritis (RA) using systematic review and meta-analysis technique. Methods: Potentially eligible studies were identified from Medline and EMBASE databases from inception to May 2020 using search strategy that comprised of terms for “Asthma” and “Rheumatoid arthritis”. Eligible cohort study must consist of one cohort of patients with asthma and another cohort of individuals without asthma. Then, the study must effect estimates with 95% confidence intervals (95% CIs) comparing incident RA between the groups. Eligible case-control studies must include cases with RA and controls without RA. Then, the study must explore their history of asthma. Odds ratio (OR) with 95% CIs of the association between asthma status and RA must be reported. Point estimates with standard errors were retrieved from each study and were combined together using the generic inverse variance method. Results: A total of 22,442 articles were identified. After two rounds of independent review by three investigators, six cohort studies and fourteen case-control studies met the eligibility criteria and were included into the meta-analysis. Meta-analysis of cohort studies found that patients with asthma had a significantly higher risk of RA compared with individuals without asthma with the pooled hazard ratio of 1.42 (95% CI, 1.18 – 1.70). Meta-analysis of case-control studies revealed that patients with asthma had a higher risk of RA compared with individuals without asthma with the pooled odds ratio of 1.33 (95%CI, 0.97 – 1.83). Funnel plot for the meta-analysis of case-control studies was asymmetric, suggesting the presence of publication bias. Conclusions: This systematic review and meta-analysis found a significant association between asthma and higher risk of incident RA.